The Influence of Social-Emotional Learning (PSE) on Critical Thinking and Learning Achievement in Grade 5 Mathematics Subjects at SD Negeri Sidareja 01 Sidareja District - Tri Prayitno; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
Education is not only about mastering academic material but also about developing social and emotional skills essential for life success. This study aims to explore the influence of integrating social and emotional learning (SEL) on students' critical thinking and academic achievement. This research used a quasi-experimental method with a nonequivalent control group design. The subjects were 5th-grade students at SD Negeri Sidareja 01. The analysis results showed that social and emotional learning (SEL) had a significant positive impact on improving critical thinking skills and academic achievement in Mathematics. The experimental class following the SEL method demonstrated a higher increase in posttest scores compared to the control class. Statistical tests indicated that the data did not follow a normal distribution, but the variance between groups was homogeneous. Therefore, this study supports the hypothesis that SEL positively influences students' critical thinking and academic achievement.